Supplemental O2 during recovery does not improve repeated maximal concentric-eccentric strength-endurance performance in hypoxia - Dünnwald, T.; Morawetz, D.; Faulhaber, M.; Gatterer, H.; Birklbauer, C.; Koller, A.; Weiss, G.; Schobersberger, W. (The Journal of Strength and Conditioning Research, 2022)
An alpine ski racing training session typically includes repeated bouts of maximal exercise at high altitude. We evaluated whether hyperoxic recovery between 5 sets of high-intensity strength-endurance exercises, which resembled ski racing activity and were performed in hypoxia, has beneficial effects on performance and acid-base status. In this randomized, single blinded crossover study, 15 highly skilled ski athletes (4 f/11 m; 29.7 ± 5.7 years) performed 5 90 seconds flywheel sets (S) in a normobaric hypoxic chamber (3,500 m). The flywheel sets were separated by 4 15-minute recovery periods. During recovery, subjects received either 100% O2 (hyperoxic setting [HS]) or hypoxic air (nonhyperoxic setting [NHS]; FiO2: 0.146). Performance outcomes (e.g., power output [PO], concentric peak power [Conpeak], and eccentric peak power [Eccpeak]) and physiological parameters (e.g., heart rate, blood gases, and blood lactate) were evaluated. Mean PO, Conpeak, and Eccpeak from S1 to S5 did not differ between settings (146.9 ± 45 W and 144.3 ± 44 W, 266.9 ± 80 W and 271.2 ± 78 W, and 271.0 ± 93 W and 274.1 ± 74 W for HS and NHS, respectively; p = 0.05). SpO2, PaO2, and CaO2 were higher during recovery in HS than in NHS (p = 0.001). Lactate levels were significantly lower in the last recovery phase in HS than in NHS (p = 0.016). Hyperoxic recovery has no impact on performance in a setting resembling alpine ski racing training. Positive effects on arterial oxygen content and cellular metabolism, as indicated by reduced blood lactate levels during recovery in the hyperoxic setting, seem to be insufficient to generate a direct effect on performance.